Impact of pharmaceutical care in the orthopaedic department. (4th December 2019) - Xie, Chengxin; Mu, Xiaoping; Hu, Zhuangming; Wang, Wei; Huang, Wenwen; Huang, Ge; Wang, Chenglong; Yin, Dong
Abstract: What is known and objective: In the mid‐1960s, clinical pharmacy developed in the USA, and as the demand for pharmaceutical services continued to grow, their impact began to be taken seriously. However, the participation of clinical pharmacists as members of the multidisciplinary team in the orthopaedic department is still in its infancy, although its role in orthopaedics has not been defined. The object of this study was to identify and discuss the impact of pharmaceutical care in the orthopaedic department. Methods: A literature search was conducted on MEDLINE, PubMed, Web of Science, the Cochrane Library and CNKI (China National Knowledge Infrastructure) for papers published between 1998 and 2019, using the keywords pharmacy, pharmacist, and medication or drug combined with orthopaedic. Other available resources were also used to identify relevant articles. Results and discussion: Based on the available evidence in 74 articles, it was found that clinical pharmacists play an important role in all aspects of rational use of medications, medication review and reconciliation, monitoring adverse drug events, risk assessment, and medication education and counselling. In addition, clinical pharmacy services were developed to minimize medication errors, adverse drug events and medical costs, but clinical pharmacy is still in its early stages in orthopaedics. What is new and conclusion: A multidisciplinary approach should be adopted in the orthopaedic department, as pharmacist interventions can be vital for promoting the safety, effectiveness and cost‐effectiveness of pharmacotherapy. Although pharmacists' contributions to orthopaedics are not yet fully recognized, pharmaceutical services can undoubtedly contribute to both clinical and societal outcomes. Abstract : Clinical pharmacists play an important role in all aspects of rational use of medications, medication review and reconciliation, monitoring adverse drug events, risk assessment, and medication education and counselling, which can be vital for promoting the safety, effectiveness and cost‐effectiveness of pharmacotherapy.